Implementasi Algoritma Blake2s untuk Mekanisme Caching Key Value pada REST API - Rifqi Raditya Wibowo; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The development of information technology today has affected all aspects of human life. There is an exchange of information every second on the internet. RESTfull API / REST API describes the embodiment of the API (application protocol interface). The REST API has a weakness in terms of security standardization for accessing data on the REST server side, this causes anyone to access, edit and delete the data contained in the REST server.MD5 is a type of Cryptographically secure hashing which has a one-way hash function. MD5 is often used to store passwords, if the cracker is able to enter and change a secret website database and then the cracker performs attacks such as SQL Injection, DDOS so that it penetrates the database and gets the password in the form of an MD5 encrypted hash then it is easy to decrypt it into plaintext to get the password. which are actually.The BLAKE2S algorithm itself was released in 2012. The BLAKE2S algorithm is built with the HAIFA iteration which has resistance to generic attacks such as herding. The BLAKE2S algorithm has a better security level than SHA-256. This research implements the BLAKE2S Algorithm for the key value caching mechanism in the REST API. The test was conducted to measure the speed of the BLAKE2S Algorithm in processing key value caching. Testing is done by running a request on the REST API twelve times to measure the caching time. The test results show that the caching time on the BLAKE2S Algorithm has a faster time than the MD5 Algorithm with a time difference of 5.6 ms.